Plastic Waste Management Policy in Support of Sustainable Development Goal 12 “Responsible Production and Consumption”: A Case Study of Surabaya City - Sabil Sabil; Helen Dian Fridayani; Achmad Nurmandi (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
Plastic waste management is one of the main environmental challenges in Indonesia, especially in the city of Surabaya. This qualitative study aims to review and analyze the implementation of government policies in creating and implementing plastic waste management to support SDG 12 (Responsible Production and Consumption). This study raises the issue of the limited effectiveness of policies in reducing plastic waste and increasing community participation. Secondary data was collected from various sources, such as Surabaya City government policy documents, scientific journals, and relevant publications. This study contributes to strengthening the understanding of the importance of a collaborative approach in the implementation of waste management policies. However, challenges such as low public awareness and weak supervision still exist. This study highlights the importance of cross-sector collaboration in strengthening plastic waste management policies. The researchers recommend that the government should increase awareness campaigns on waste sorting and recycling. Additionally, stricter oversight is needed to limit the use of single-use plastic waste as part of the strategy to achieve SDG 12 at the city level.